PENDIDIKAN KEAKSARAAN FUNGSIONAL DAN DAMPAKNYA TERHADAP AKTUALITAS PROFESI WARGA MASYARAKAT - Rahman, Misran (JIV-Jurnal Ilmiah Visi, 2013)
The purpose of this research is to describe the implementation of functional literacy education towards the professional actuality of the community members in Kayumerah village, Lomboto Subdistrict, Gorontalo District. The research conducted as from April through June 2013, collected data by interviewing 20 resource persons with various professional backgrounds. The data were analysed qualitatively and concluded that the participants of functional literacy education are motivated to complete the program and the result has significant effect to do their jobs.